Answer:
is there a picture to this problem?
Go to cymath and type it in and it will work it out for you and tell you the answer
Answer:
(4, 5)
Step-by-step explanation:
Calculate the midpoint using the midpoint formula
midpoint = [( + ), ( + ) ]
with (, ) = (1, 2) and (, ) = (7, 8)
midpoint = [(1 + 7), (2 + 8) ]
= (4, 5)
Answer:
X=-3/8 (x equals negative 3 over 8.)
Step-by-step explanation:
So, you have twice a number and six. That is going to be 2x*6, and that then simplifies into 12x. Now, 11 times the number, would be 11x. The difference between 11x and 3/8 would be 11x-3/8.
So, You now have 12x=11x-3/8.
Combine like factors. So, 12x-11x=-3/8.
Now, you have x=-3/8.
Hope this Helps!! (: